Configuration of a unique antibacterial needle-punched nonwoven fabric from silver impregnated polyester nanocomposite fibres. Issue 1 (June 2022) - Gadkari, Rahul Rajkumar; Ali, Wazed; Das, Apurba; Alagirusamy, Ramasamy
The current study aims to mitigate the problems arising due to leach-out of silver nanoparticles (Ag-NPs) from an antibacterial material developed using silver coating or finishes. Polyester (PET) staple fibres with Ag-NPs firmly integrated within them were used to prepare needle-punched nonwoven fabric. To further enhance the antibacterial efficiency, the nonwoven surface was etched via alkaline hydrolysis such that the Ag-NPs are exposed to the bacterial cell wall. The antibacterial activity of the nonwoven made of PET-Ag-NPs nanocomposite fibres (P/Ag-NFs) against S. aureus and E. coli bacteria was found to be increased after hydrolysis by 4.5% and 6.5%, respectively. The amount of silver leach-out from the developed antibacterial media was 0.01 ppm for 24 h immersion time, which is in compliance with regulations of National Institute for Occupational Safety and Health (0.01 mg/m 3 ), as well as that of WHO (0.1 ppm). Moreover, the nonwoven was effective in killing up to 94% and 98% S. aureus and E. coli bacteria, respectively. Hence, the developed nonwoven fabric can safely be used for medical and health care textiles, antibacterial clothing and for the development of dry/wet filtration media.